Modul Organization of Learning the Course of „Psychology” in Higher Educational Establishments of I-І I Levels of Accreditation - Mandryko, Tamara (Pedagogical Discourse, 2011)
Opportunity of using module learning of the course „Psychology” and its advantages over traditional system of studying is studied in the article.